Best Answer

Not sure how the problem is set up as I see a space between the minus sign and the 12 but not between the minus and the 2. But, using the numbers as written: To solve for b, you must form an equation (-5b -12 -2 = 0). Next you must separate the known numbers from the unknown by adding the sum of the knowns to both sides of the equation (-5b = 14). Then divide both sides of the equation by -5 to find the value of b (b = -2.8). No no no no no. It is -5b-14 because the -5b has no relation to the others so it stays as it is and then -12-2=-14 thus getting -5b-12-2=-5b-14. Cool.

Study guides

☆☆

Q: -5b - 12 -2

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

To solve for b, you must form an equation (-5b -12 -2 = 0). Next you must separate the known numbers from the unknown by adding the sum of the knowns to both sides of the equation (-5b = 14). Then divide both sides of the equation by -5 to find the value of b (b = -2.8).

No. 7b - 2b = 5b

2

8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3

Let a + bi be the reciprocal. So (a + bi)(2 - 5i) = 1 (a + bi)(2 - 5i) = 2a - 5ai + 2bi + 5b = (2a + 5b) + (2b - 5a)i Therefore 2a + 5b = 1 and 2b - 5a = 0. Solving the simultaneous equations, we find that a = 2/29 and b = 5/29. So the reciprocal of 2 - 5i is 2/29 + 5i/29.

Related questions

5b + 5b = 2 x 5b

(1) 4a-5b=7 (2) 4a+5b=17 (1)-(2) gives 4a-5b-(4a+5b)=7-17 then -10b=-10 so b=1 from (2) one gets 4a=17-5b=17-5x1=12 so a=3 (3,1) is the solution

5b + 21b = 1226b = 1226 26b = 12/26

To solve for b, you must form an equation (-5b -12 -2 = 0). Next you must separate the known numbers from the unknown by adding the sum of the knowns to both sides of the equation (-5b = 14). Then divide both sides of the equation by -5 to find the value of b (b = -2.8).

4(5b - 6a^2)(5b + 6a^2)

No. 7b - 2b = 5b

12 and 60 ============ a + b = 72 a = 5b replacing a by 5b in the first equation 5b + b = 72 6b = 72 b = 12 72 - 12 = 60

2

You have to be 12 years old and you also have to be in year 7.

5b plus 5-3b-7 is 2b-2.

(a^2 + 8b)(a^2 - 5b)

5ab-2ab+4a-b+5b = 3ab+4a+4b

People also asked